1985
DOI: 10.1093/bja/57.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Barbiturates in Brain Ischaemia

Abstract: This review has indicated that barbiturates are useful in controlling ICP during anaesthesia in patients with intracranial hypertension. While laboratory data indicate that intraoperative administration of barbiturates during episodes of transient cerebral ischaemia, associated with surgical revascularization procedures, should be efficacious, current intraoperative results claiming benefit are anecdotal. Continuous high-dose barbiturate therapy (induced barbiturate coma) for occlusive stroke and persistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(22 citation statements)
references
References 59 publications
0
18
0
4
Order By: Relevance
“…The use of thiopental during deep hypothermic circulatory arrest is based on animal studies of ischaemia models and on its clinical use in a neurosurgical setting. These data have been reviewed by Shapiro and Belopavlovic & Buchthal [5,6]. Some animal studies have shown a decrease in infarct volume, neurological deficit and death after deep hypothermic circulatory arrest in a variety of species pretreated with high-dose thiopental (50 mg.kg )1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of thiopental during deep hypothermic circulatory arrest is based on animal studies of ischaemia models and on its clinical use in a neurosurgical setting. These data have been reviewed by Shapiro and Belopavlovic & Buchthal [5,6]. Some animal studies have shown a decrease in infarct volume, neurological deficit and death after deep hypothermic circulatory arrest in a variety of species pretreated with high-dose thiopental (50 mg.kg )1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal plasma lev els as high as 380 f.LM (Hoff et al, 1975) and brain levels as high as 200 f.LM (Krieglstein et al, 1981) have been reported. In human trials with thiopental, serum concentrations of 60--200 f.LM have been doc umented (Shapiro, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…, 1981Selman et aI. , , 1982 have also been re ported (reviewed by Piatt and Schiff, 1984;Shapiro, 1985;Trauner, 1986). Clinical studies have sug gested that barbiturates are not helpful in patients suffering cardiac arrest (Abramson et aI., 1986) or head trauma (Ward et aI., 1985).…”
mentioning
confidence: 99%
“…anaesthetic agents depress also cerebral metabolism in a dose-dependent manner. As typified by the barbiturates, this depression is associated with a reduction in cerebral metabolic requirements for oxygen (CMRo 2 ) and CBF, which stabilize when electroencephalographic (EEG) activity becomes isoelectric [6,7]. Barbiturate-induced cortical suppression has been advocated as a method of cerebral protection during temporary occlusion of any vessel that provides nutrients to the central nervous system [8].…”
mentioning
confidence: 99%